Konstruksi Masyarakat tentang Penerapan Protokol Kesehatan Pada Masa Pandemi Covid-19 - Hesty Kartikasari; Agita Berlian Oktantia; Fransiscus Xaverius Sri Sadewo (Jurnal Community, 2022)
The Covid-19 pandemic has brought many changes in people's lives. People's habit patterns have changed since the world was declared in a pandemic condition. The government has made various efforts to suppress the spread of the virus, such as work from home, PSBB and PPKM. People are encouraged to minimize activities outside the home.  The public is also recommended or even now it is a must to apply the health protocols set by WHO to avoid exposure to the virus. This study aims to identify the objective and subjective meanings and the internalization process related to the application of health protocols during the pandemic. The method used is descriptive qualitative. Data was collected by observation and in-depth interviews with informants. This research was assisted by the theoretical foundation of social construction belonging to Peter L. Berger and Thomas Luckman. The results state that the process of the externalization stage can be seen when the community begins to adapt to pandemic conditions by implementing health protocols as a form of self-protection so as not to be infected with the virus. Then the objectification is seen from the people who run the health protocols to avoid the virus. Finally, the internalization stage where the public has understood the dangers of the corona virus and the importance of implementing health protocols obtained through socialization.